Studi Pengaruh Endorsement dan Advertising Campaign terhadap Brand Image Scarlett Whitening pada Instagram Bunga Cosmetics Kota Gorontalo - Zihan Putri Maharani Montu; Ramlan Amir Isa; Andi Juanna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out how much influence Endorsements and Advertising Campaigns have on Scarlett Whitening's Brand Image on Instagram Social Media (Study on Scarlett Whitening Bunga Cosmetics Agent, Gorontalo City).